Web-Based Waste Management Information System Using the Waterfall Method - Muhamad Noviadih; Adam Muiz; Dede Sunandar (Komunitas Dosen Indonesia, 2026)
The rapid growth of urbanization and industrial activities has significantly increased waste generation, posing complex environmental and operational challenges when information management remains fragmented across institutions. This study aims to design and implement a web-based waste management information system to support integrated waste handling processes at the Environmental Agency of Tangerang Selatan. The system was developed using the Waterfall method, encompassing requirement analysis, system design, implementation, testing, and maintenance, with data collected through observation, stakeholder interviews, and literature review. UML modeling was employed to formalize system architecture, and the application was implemented using Laravel (PHP) and MySQL. The proposed system introduces a unified platform that integrates citizen reporting, institutional workflow management, and public information dissemination, addressing limitations of prior web-based systems that are typically function-specific and lack cross-stakeholder integration. The system supports waste reporting, processing, and monitoring within a closed-loop workflow, enhancing traceability and coordination. Quantitative evaluation through functional testing achieved a 100% success rate across all core modules, while preliminary operational observations indicate reduced reporting delays and improved data accessibility compared to prior manual processes. The system also enhances public engagement through structured reporting and educational content delivery. These findings demonstrate that the system provides measurable improvements in operational efficiency and stakeholder coordination, offering a scalable and cost-effective digital governance solution for municipal waste management in resource-constrained environments.